(untitled) (Journal of Governance and Development (JGD), 2023)
The objective of this paper is to examine the factors that led to the defeat of the Peoples Democratic Party (PDP) in Nigeria’s 2015 general elections after dominating Nigeria’s political landscape since the return to democracy in 1999. The methodology of the paper is qualitative and conceptual. The issues were analysed under various themes. The data were gathered through the secondary method of data collection such as textbooks, journal articles, reports of election observer teams, party constitutions, workshop papers, Independent National Electoral Commission (INEC) documents, the Electoral Acts and the 1999 Constitution of the Federal Republic of Nigeria. The analysis of the information gathered helped to dissect the circumstances that were responsible for the electoral defeat of the Peoples Democratic Party (PDP) by the current ruling All Progressives Congress (APC) in the 2015 general elections. The research discovered that some factors were responsible for the defeat of the PDP in the 2015 general elections, chief among them is the abysmal lack of internal party democracy in the party. The paper asserts that though political parties are indispensable institutions in a democracy, for them to make fundamental contributions to democracy, they must, among other things, adhere to the tenets of internal party democracy in order to sustain their electoral strength and make a profound contribution to democratic growth.